Béatrix Beck: The “Barny Cycle”: Writing to Inform and Heal the Self - Myrna Bell Rochester; Mary Lawrence Test (Studies in 20th & 21st Century Literature, 2012)
To cope with the traumatic reality of World War II, French society repressed its memories, resulting in a false collective memory. Today, a more truthful history can be restored with the study of wartime and post-war texts. We examine the first six books (1948-67) of Belgian-French writer Béatrix Beck (1914-2008), alongside the theories of psychiatrist Judith Lewis Herman, who wrote that “traumatic reactions occur when action is of no avail.” Beck’s semi-autobiographical protagonist, Barny, goes through Herman’s stages of forgetting and remembering, healing and recovery. Her emergence as a writer also follows that trajectory: Barny, like Occupied France, was isolated. Helpless to act or react, she was traumatized—by her father’s death, a dysfunctional childhood, her mother’s suicide, and, in Occupied France, her husband’s death, single motherhood, poverty, menial jobs, and fear of arrest. In the first stage of recovery, Barny reaches safety. In the second, she begins to remember, to probe the issues and articulate them, in their painful ambiguity. For Herman, the ultimate goal is to put the story, with its imagery, into words. In the third stage, Barny, against fierce odds, becomes a writer.
Keywords: World War II; repressed memories; France; war; wartime; post-war; Béatrix Beck; Judith Lewis Herman; trauma; occupied France; isolation; isolated; Barny Cycle